Der Hayek-Schmitt-Nexus. Neoliberalismus und Neue Rechte im antidemokratischen Konsens - Becher, Phillip; Rösch, Kevin (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2023)
Contrary to the widespread notion that Friedrich August Hayek’s liberal agenda is to be understood as an alternative to “authoritarian populism”, the contribution shows that this juxtaposition quickly reaches its limits. Rather, a connection of intellectual and real history, conceived as a nexus, reveals a program advocated by both Hayek and Carl Schmitt, which was skeptical of democracy to the point of being anti-democratic and which was linked with far-reaching ideas on the theory of the state. Finally, a critical evaluation of corresponding discussions in liberal and conservative literature of the past century (i.a. Wilhelm Röpke) makes it possible to understand the close relationship between supposedly anti-statist neoliberalism and the ostentatiously anti-liberal New Right in the vein of Alain De Benoist. De Benoist; Hayek; Röpke; Schmitt; Democracy; Dictatorship; Elite; Neoliberalism; New Right; Ordoliberalism; Theory of the State.